Community-Based Research-Based Moringa Corn Milk Innovation for the Prevention of Anemia in Adolescent Girls in Orphanages - Meta Rikandi; Asmeri Lamona; Chintia Pratama Putri; Suci Sintia Dewi; Silvia Nengcy; Esiska Afifah; Thalia Natami; Linda Wati (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Anemia in adolescent girls remains a public health problem that impacts cognitive function, productivity, and future reproductive health. Adolescent girls in orphanages are a high-risk group due to limited access to nutritious food and low nutritional literacy. This paper is a research-based community service project that uses a Community-Based Research (CBR) approach to develop an anemia prevention intervention model through the integration of nutrition education and local food innovation in the form of moringa-corn milk. The activity was carried out in an orphanage in Padang City on September 4–14, 2025, involving 24 caregivers and 30 adolescent girls. The CBR stages included needs assessment, co-designed intervention, collaborative implementation, and participatory evaluation and sustainability strengthening. Nutrition education was provided to the caregivers with pre- and post-tests, followed by training on making moringa-corn milk and testing its acceptability among the adolescent girls. The results showed a significant increase in the caregivers' knowledge, marked by an increase in the good knowledge category from 17% to 46%. Organoleptic testing showed that 40% of the adolescents said they somewhat liked the product and 26.67% said they really liked it. These results show that moringa-corn milk innovation is well accepted and has the potential to be an economical and applicable alternative source of iron. The novelty of this program lies in the integration of nutrition education, community empowerment, and CBR-based local food innovation, thereby increasing community capacity while strengthening the sustainability of anemia prevention interventions in adolescent girls in orphanages.